Versatile Multimodal Solutions the anatomy of user interaction. - Hosn, Rafah (XML journal :the ultimate enterprise resource.)
User interaction is about creating an effective man-machine conversation that leads to rapid task completion. With this in mind, we can factor the typical application into the data model that holds the current interaction state, user interface components that render this state and interaction behavior that is determined by the active event handlers.